Differential response of winter- and summer-emerging accessions of rigid ryegrass (Lolium rigidum Gaudin) to postemergence herbicides in Australia. (22nd October 2022) - Chauhan, Bhagirath S.; Walsh, Michael
Abstract: Rigid ryegrass is a problematic weed species in winter crops and winter fallow; however, recently, this weed species has been observed in summer crops and fallow. These observations warrant the evaluation of different postemergence herbicides for its control. Outdoor pot studies were conducted during the spring and summer of 2021 to 2022 to determine the performance of POST herbicides on two summer-emerging (S3 and S6) and two winter-emerging (W3 and W8) accessions of rigid ryegrass. Across all accessions, butroxydim, clethodim, paraquat, and paraquat + amitrole at the field rate provided complete control of rigid ryegrass. Both summer-emerging accessions were found to be resistant to the field rates of glufosinate (750 g ai ha −1 ), glyphosate (454 g ae ha −1 ), haloxyfop (52 g ai ha −1 ), and pinoxaden (30 g ai ha −1 ). The S6 accession had the highest dose required for a 50% reduction in biomass for these herbicides (glufosinate 1, 120 g ai ha −1, glyphosate 1, 210 g ae ha −1, haloxyfop 140 g ai ha −1, and pinoxaden 55 g ai ha −1 ). This summer-emerging accession (S6) was also resistant to iodosulfuron. All four accessions were found susceptible to imazamox + imazapyr (a commercial mixture) and mesosulfuron. The study provides the first evidence of poor control of summer-emerging accessions of rigid ryegrass with different herbicides. Multiple-herbicide-resistant summer-emerging rigid ryegrass accessions would be a challenge to the production of summer crops (e.g., cotton and sorghum) as well as winter crops that rely on weed-free summer fallows for soil moisture retention; therefore these accessions warrant diversified management strategies.